Os ethé discursivos da cena enunciativa jurídica cível: uma análise da petição inicial, da contestação e da sentença no processo civil - Souza, Fernando Leandro De [UNIFESP] (2020)
The present work aims to analyze the constitution of the discursive ethos, as conceived by Maingueneau (2008, 2013, 2015, 2018), in the civil legal enunciative scene. It is part of the research line “Language in new contexts” of the Postgraduate Program in Letters at the Federal University of São Paulo and adds to the linguistic studies the discourse analysis of the legal field. To this end, it conducts a qualitative analysis of an initial application, a challenge and a sentence, which make up the same lawsuit in the civil area, within an ordinary procedure. These three documents constitute the research corpus. Through the intersection of thoughts of the Discourse Analysis theorists, especially those of the French line, the aim is to analyze the linguistic-discursive resources used for the constitution of the enunciator's discursive ethos in the three mentioned speech genres and the degree of interference that these resources exert in the adhesion of the recipients. It starts with the hypothesis that the enunciators work to transmit a good image of themselves, in search of a specific objective, and that some individuals who assume certain discursive roles see the need to transmit a distinct image of themselves as an obligation, as those belonging to the discursive fields of law. Allied to the study of ethos, we intend to investigate the scenes of enunciation, theorized by Maingueneau (2015), namely the encompassing scene, the generic scene and the scenography, in order to situate the chosen genres within the discursive universe to which they belong, as well as studying polyphony, under the same author's view, to understand the use of the authority argument, and to discourse on the institutional ethos, to understand the relationship of symbolic exchanges between individuals who assume the discursive roles surrounding the elected genres and their respective institutions. The results show a preference for erudite, solemn, eloquent and combative ethé, among others, belonging to the stereotypes of judge and lawyer, marked by argumentative linguistic resources, abuse of pronouns of treatment, appreciation of pompous language, polyphonic appeal to voices of authorities outside the utterances and by the deliberative language.